Emerging roles of exosomal miRNAs in breast cancer drug resistance. Issue 11 (19th July 2019) - Najminejad, Hamid; Kalantar, Seyed Mehdi; Abdollahpour‐Alitappeh, Meghdad; Karimi, Mohammad Hossein; Seifalian, Alexander M.; Gholipourmalekabadi, Mazaher; Sheikhha, Mohammad Hasan
ABSTRACT: Breast cancer (BC), as a heterogeneous disease, is considered as one of the most common malignancies in women worldwide. The resistance of BC cells to therapeutic agents has remained a big challenge in the treatment of BC patients. Some factors such as cytokines, exosomes, and soluble receptors were recognized as crucial agents involved in the development of drug resistance. However, the exact mechanisms underlying the drug resistance is still unknown. There is growing evidence to support the emerging roles of exosomes, especially exosomal miRNAs, in tumor initiation, angiogenesis, proliferation, migration, invasion, metastasis, and drug resistance. Therefore, identification of BC‐specific exosomal miRNAs and their underlying mechanisms would be helpful to define sensitivity to therapeutic drugs and establish an appropriate therapeutic strategy. This review focuses mainly on the roles of exosomal miRNAs and their associated mechanisms in the resistance of BC cells to therapeutic agents, as well as critically examines the potential of these macromolecules as a treatment biomarker in BC patients.